Dry matter accumulation, translocation, and bulb yield of short-day onion as affected by cultivars and drip irrigation regimes in the dry-hot regions of southwest China - Yilin Li; Jiancha Li; Binyan Zhang; Xuewen Yue; Kun Li; Daming Chen; Yujiao Yang; Xiaogang Liu; Haidong Fang (Agricultural Water Management)
Seasonal water scarcity and improper cultivar selection have severely restricted the production potential of short-day onions in the dry-hot regions of southwest China. However, the appropriate irrigation regime and cultivar are still unclear. Therefore, field experiments were conducted during the two onion growing seasons (2022–2023 and 2023–2024) to evaluate the effects of irrigation levels [full irrigation (W1: 100 %ETc) and three deficit irrigation levels (W2: 80 %ETc, W3: 60 %ETc and W4: 40 %ETc); where ETc was crop evapotranspiration] on aboveground dry matter accumulation, partitioning, translocation, bulb yield and irrigation water productivity (WPI) of different onion cultivars [a local traditional cultivar (C1: Hongshuai) and two new cultivars (C2: Niu 4 and C3: Shahu)]. The results showed that the logistic growth model could effectively fit the process of dry matter accumulation in onions. C2 and C3 reduced aboveground dry matter accumulation, maximum accumulation rate of dry matter (ARmax), and average accumulation rate of dry matter (ARavg), but increased bulb yield and WPI when compared with C1. Notably, C2 had the highest bulb yield and WPI in the two growing seasons. Deficit irrigation decreased dry matter accumulation after bulb initiation (DMAI), but increased bulb dry matter proportion and dry matter translocation (DMT). Bulb yield under W1 and W2 had insignificant difference, but W2 enhanced WPI. Although W3 and W4 significantly increased WPI, bulb yield decreased significantly. Bulb dry matter had significantly positive correlation with DMAI. Comprehensively considering bulb yield and WPI, the ‘Niu 4’ cultivar was preferred and an irrigation amount of 80 %ETc (onion evapotranspiration) was recommended for onions production in the dry-hot regions of southwest China. By optimizing the irrigation strategy of onions, WPI can be improved without significantly reducing bulb yield, which is of great practical significance for dry-hot regions with water scarcity. This study can provide a theoretical basis for optimizing onions irrigation management and cultivar selection in the dry-hot regions.